Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5530/ijper.51.3s.5
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Mentha piperita L. Extracts Against Bacteria Isolated from Soccer Player’s Shoes and its Antioxidant Activities

Abstract: Objective: Microorganisms have an easier entry into the sportsman's epidermis, and these make diseases on athletes. The main scope of the study is to search the lack of information about the biological activities of Mentha piperita extracts against bacteria isolated from soccer player's shoes. Materials and Methods: The bacteria were isolated from soccer player's shoes from Balikesir Spor soccer team after the competition. The plant extracts were tested by disc diffusion assay for antibacterial activity. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…In another study, Ceylan et al () reported to display a maximum zone of inhibition against Staphylococcus aureus (15 mm) and Pseudomonas aeruginosa (15 mm) as depicted by disc disc diffusion/ dilution method in vitro. In the literature, some works also have been reported on anti‐bacterial activity against various microorganisms (Bassolé et al, ; Vivek et al, ; Hussain et al, ; Tyagi & Malik, ; Jeyakumar et al, ; Sujana et al, ; Addai, Addai, ; Pulipati et al, ; Patil et al, ; Okmen et al, ).…”
Section: Pharmacological Activities Of M × Piperitamentioning
confidence: 99%
“…In another study, Ceylan et al () reported to display a maximum zone of inhibition against Staphylococcus aureus (15 mm) and Pseudomonas aeruginosa (15 mm) as depicted by disc disc diffusion/ dilution method in vitro. In the literature, some works also have been reported on anti‐bacterial activity against various microorganisms (Bassolé et al, ; Vivek et al, ; Hussain et al, ; Tyagi & Malik, ; Jeyakumar et al, ; Sujana et al, ; Addai, Addai, ; Pulipati et al, ; Patil et al, ; Okmen et al, ).…”
Section: Pharmacological Activities Of M × Piperitamentioning
confidence: 99%
“…Mentha × piperita L. is a cultivated natural hybrid of Mentha aquatica L. (water mint) and Mentha spicata L. (spearmint), both native species of the Mediterranean region. M. Piperita is cultivated worldwide because its EO has antioxidant and antimicrobial activities and is used as eco-friendly pesticide [ 24 , 25 ]. Likewise, the phytotoxic activity of M. piperita EO has been demonstrated in several studies [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, spearmint essential oil has economic relevance due to its use in perfumery, confectionary, cosmetics and pharmaceutical preparations. The fresh and dried spearmint leaves have been used as a flavoring agent in various food products, including cheese and dough (Iranian yoghurt drink), chocolate, beverages, jellies, syrups, candies, ice creams, and chewing gum [32].…”
Section: Introductionmentioning
confidence: 99%